Design Of Liquid Smoke Equipment With A Capacity Of 120 Ml Per Hour - Bakri Anuar, Bakri; Muchlisinalahuddin,; Malikil Kudus Susalam,; Ilham Alghani,; Reyhan Stevano, (IJIMCE : International Journal of Innovation in Mechanical Construction and Energy, 2025)
<!--StartFragment--> Liquid smoke is the result of pyrolysis of various types of biomass used in various industrial applications, including food preservation and waste treatment. This study aims to design and test a liquid smoke production device with a capacity of 120 ml per hour using six types of raw materials: coconut husk, coconut shell, straw, rice husk, corn cob, and corn stalk. The graph of the test results shows that the second experiment (test 2) produced a higher volume of liquid smoke than the first experiment (test 1), with the maximum volume reaching 310 ml. Nonetheless, the processing time varies depending on the type of raw material used. The results of this study show that optimizing the pyrolysis process can improve the efficiency of liquid smoke production, both in terms of volume and processing time. Thus, the device design used in this study has the potential to be further developed to increase production capacity and efficiency. Keywords: liquid smoke, pyrolysis, equipment design, production capacity, coconut shell. <!--EndFragment-->